An Implementation of Ant Colony and Genetic Algorithm based Hybrid-Metaheuristic for Cut-off Grade Optimization in Open-Pit Mining Operations - Qureshi, Muhammad Asim (Curtin University, 2017)
This study presents a new mathematical model for cut-off grade and production scheduling optimisation in open pit mining operations. The model maximises the net present value of the operation subject to the mining precedence, production capacity, and grade-blending constraints. A solution using exact method establishes the computational complexity of the model. Consequently, a hybrid-metaheuristic is developed to solve practical instances of the model. Performance evaluation reflects an acceptable gap between the exact and heuristic solutions.